Development of Digital Electronics and Information Literacy Training Kit to Improve the Performance of Students Electrical Engineering Education - Nur Kholis; M. Syarifuddin Zuhrie; Dirman Hanafi Burhanuddin (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: The study aims to develop a digital electronics kit and information literacy to improve student performance in terms of validity and reliability in terms of language and materials. Analyze student responses to the digital electronics kit and information literacy. Analyze student performance results and the relationship between variables. Method: The method used in the study includes the research stage. The study was conducted to determine what competency standards and essential competencies are expected. Novelty: Kits and information literacy were developed to support skills in facing the demands of industrial technology 4.0. Connecting students with industry through the latest kits and learning modules, strengthening the relationship between academia and industry. Research results: Cronbach's alpha reliability test results are higher than its fundamental value, 0.820> 0.60. The results prove that all statements in the information literacy variable are reliable. The analysis of student responses to devices and information literacy obtained an average value of 90%, and student performance results from several criteria averaged 87.1; the kit has a significant and positive contribution (<0.10) and a path coefficient value of 0.102. The results of data analysis have proven that information literacy has a significant and positive contribution (<0.10), and the path coefficient value is 0.077.